Can an Elusive Platinum(III) Oxidation State be Exposed in an Isolated Complex?. (11th August 2020) - Corinti, Davide; Frison, Gilles; Chiavarino, Barbara; Gabano, Elisabetta; Osella, Domenico; Crestoni, Maria Elisa; Fornarini, Simonetta
Abstract: Platinum(IV) complexes are extensively studied for their activity against cancer cells as potential substitutes for the widely used platinum(II) drugs. Pt IV complexes are kinetically inert and need to be reduced to Pt II species to play their pharmacological action, thus acting as prodrugs. The mechanism of the reduction step inside the cell is however still largely unknown. Gas‐phase activation of deprotonated platinum(IV) prodrugs was found to generate products in which platinum has a formal +3 oxidation state. IR multiple photon dissociation spectroscopy is thus used to obtain structural information helping to define the nature of both the platinum atom and the ligands. In particular, comparison of calculations at DFT, MP2 and CCSD levels with experimental results demonstrates that the localization of the radical is about equally shared between the dxz orbital of platinum and the pz of nitrogen on the amino group, the latter acting as a non‐innocent ligand. Abstract : Formal platinum(III) complexes obtained after collisional activation of Pt IV prodrugs are assayed using IR ion spectroscopy to identify vibrational features characteristic of their electronic structure. The role of the non‐innocent NH2 ligand in the formation of these elusive Pt III complexes is discussed on the basis of spin natural orbital analyses.